IDENTIFIKASI DAERAH RESAPAN AIR DENGAN SISTEM INFORMASI GEOGRAFIS (STUDI KASUS: SUB DAS KEDUANG) - Fajar Dwi Hastono; Bambang Sudarsono; Bandi Sasmito (Departement Teknik Geodesi Universitas Diponegoro, 2012)
Sub Watershed Keduang is part of the Upper Solo River Basin which includes the area of the river solo. Degradation of the territory of its recharge area is the cause of the damage of Solo River Watersheds, especially upstream of Solo resulting in the decreasing availability of water resources in the area. The aims of this study is determine the conditions and potential water recharge areas are located in Sub Watershed Keduang. The methods that use in scoring and to overlay (Overlapping stacking) method between the type of soil maps, land use maps, maps of slope and rainfall maps. Watershed maps obtained from the four overlay map. Identification of water recharge areas is done using a Geographic Information System (GIS) that can be used as a material consideration to doing conservation and rehabilitation the land and the forest. The results showed that to all criteria conditions are scattered throughout the recharge area of river basin Sub Keduang but in general Sub Watershed Keduang have recharge conditions including the start of critical criteria. The results of the analysis area of Keduang Sub Watershed is 39736.44 Ha. The areas that have good conditions recharges area of 1489.77 ha (3.75%) and recharge areas that become critical condition of 13505.04 ha (33.99%). Watersheds are in critical condition a little area of 11407.5 ha (28.71%). Criteria of normal water absorption natural conditions, a critical and very critical that each area are 5816.7 ha (14.64%), 5187.24 ha (13.05%) are 2330.19 ha (5.86%). Potential areas in the recharge area of research in Keduang sub Watershed dispersed in good condition with a wide recharge area of 1489.77 ha (3.75%) and normal conditions of natural water recharge area with an area of 5816.7 ha (14.64%). Territory of its potential recharge area is scattrered in the District's area of 313.2 ha Jatiyoso and 1645.45 ha that is located in the District Jatiroto.